Konstruksi Realitas Konflik Industri Penerbangan Framing Pemberitaan Konflik Traveloka vs Airasia di detik.com - Euis Komalawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Entering into 2019, the public users of air transportation services were shocked by various reports on issues related to the aviation industry, from rising avtur prices, high domestic flight tickets, the elimination of free baggage services to competition and penetration of foreign airlines. One of the news in online media that attracted public attention was the conflict between AirAsia and Traveloka as an online travel agent (OTA). For this reason, this study was carried out to analyze the conflict reporting framing of Traveloka vs AirAsia in Detik.com online media. This study used a qualitative method with Robert N. Entman's framing analysis approach. The unit of analysis in this study was 5 news texts about the conflict of Traveloka vs AirAsia on Detik.com media. The results of the study refer to the four elements of framing Entman. The first, defining the problem that the loss of AirAsia ticket distribution at Traveloka is due to problems with business to business and the alleged pressure of national airlines. The second, source of problems (Diagnose Causes) is Traveloka due to the pressure of the national airline. The third, the moral decision (Make Moral Judgment) of this problem cannot be allowed to drag on because it is a form of discrimination. The fourth, emphasizing the settlement (Treatment Recommendation), namely the need for dialogue between the two parties mediated by the Business Competition Supervisory Commission (KPPU). The framing highlighted by Detik.com in the Traveloka vs AirAsia Conflict report was a bbusiness-to-business problem, even though there was an allegation that there had been an indication of an AirAsia ticket distribution channel due to the pressure of the national airlanes